ILLOCUTIONARY ACTS IN ERNEST PRAKASA’S MOVIE “IMPERFECT” - Karana Jaya Tarigan; Elita Modesta Sembiring; Veracy Silalahi (Fakultas Keguruan dan Ilmu Pendidikan | Universitas Islam As-Syafi'iyah, 2022)
This study aims to analyze the types of Illocutionary acts used by the characters in the movie Imperfect. This research applies qualitative descriptive method. The writer uses 65 speech acts samples from this movie and chooses them randomly to analyze the types of Illocutionary acts in this movie. It is found that there are five types of Illocutionary acts used in the movie Imperfect, namely: Representative, Directive, Commissive, Expressive, and Declarative. The total Illocutionary acts are about 157 utterances. Representative has 47 utterances, directive has 66 utterances, commissive has 4 utterances, expressive has 39 utterances, and declarative has 1 utterance. Keywords: illocutionary acts, movie